Partner in Jihad: Marriage, Women and Deradicalised Terrorists in Indonesia - Toyibah, Dzuriyatun (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2021)
The involvement of women in jihad has increased significantly in many countries including Indonesia. This changes the image that women are underrepresented in relation to acts of jihad and terrorism. Drawing from in depth-interviews with six wives of disengaged terrorists in 2016, the current article aims to explain their marriage and support in jihad.  Applying religious radicalisation frameworks ranging from pre-radicalisation to jihadisation, the participants have not achieved the final step. They mostly believe in allowing jihad in conflict-ridden countries, but not in Indonesia. Marriage and family are very important to introduce the ideology of allowing violence in conflict-ridden areas. Their husband’s affiliation to a radical group has the potential to support the wives to strengthen their network within the terrorist circle.  However, in general, the participants were not intensively engaging in religious studies (pengajian), were limited from connecting with their past friends after their husbands were sentenced. They disagreed with their husband’s dream and actions. Therefore, the potential network for continuing radicalisation will not develop very significantly.